2020
DOI: 10.1039/c9cc09784h
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced emission and solid fluorescence of fluorescein derivatives

Abstract: The AIE and strong solid fluorescence of fluorescein derivatives can be realized in a simple way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 16 publications
0
52
0
Order By: Relevance
“…While the tails do not directly influence the energy ordering of excited states, they maye nhancen on-radiativep athways due to the increased conformational flexibility. [11a, 19] Ar ecent report on fluo- rescein derivatives found that increasing the alkyl sidechain length reduced QY of the monomeric state, [20] whereas conformationall ocking typically increases the QY for conjugated chromophores. [11a, 21] Notably,x ylindein thin films exhibit relativelyh igh electron mobility as shown by the I-V curvest aken in the dark (Figure S10a), [6b] corroborating the p-p stacking and H-bonding network betweena djacent xylindein molecules (see above).…”
mentioning
confidence: 99%
“…While the tails do not directly influence the energy ordering of excited states, they maye nhancen on-radiativep athways due to the increased conformational flexibility. [11a, 19] Ar ecent report on fluo- rescein derivatives found that increasing the alkyl sidechain length reduced QY of the monomeric state, [20] whereas conformationall ocking typically increases the QY for conjugated chromophores. [11a, 21] Notably,x ylindein thin films exhibit relativelyh igh electron mobility as shown by the I-V curvest aken in the dark (Figure S10a), [6b] corroborating the p-p stacking and H-bonding network betweena djacent xylindein molecules (see above).…”
mentioning
confidence: 99%
“…As expected for AIE undergoing molecules, the aggregation process involving the self-assembly of emissive units improve fluorescence. Hydrogen bonding and van der Waals interactions are involved in the process [71]. On solutions of NBDF probe was observed the typical behaviour of AIEgens, depending on a different solvent/non-solvent ratio.…”
Section: Spectroscopic Behaviormentioning
confidence: 92%
“…As expected for AIE undergoing molecules, the aggregation process involving the self-assembly of emissive units improve fluorescence. Hydrogen bonding and van der Waals interactions are involved in the process [71].…”
Section: Spectroscopic Behaviormentioning
confidence: 99%
“…Fluorescein presents also a weak Stokes shift, the interval between highest absorption and emission wavelength, which is a potential issue for devices using a single optical path, such as entry-level plate readers. Like most intense fluorescent probes, self-quenching can occur in case of aggregation (ACQ) or high degrees of surface substitution [25]. Hopefully, due to low the concentration used in biological systems, this drawback has little relevance.…”
Section: Fluorescein: Synthesis and Propertiesmentioning
confidence: 99%